Physiological and biomechanical loads in small sided field hockey games - Wilmes, E.; de Ruiter, C.; van Leeuwen, R.; Banning, L.; van der Laan, D.; Savelsbergh, G. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: When assessing training load, a distinction can be made between physiological and biomechanical load [1]. The physiological load of field hockey is known to vary with different formats of small sided games (SSGs) [2]. However, little is known about the biomechanical loads of field hockey SSGs. Therefore, the aim of present study was to gain a more thorough understanding of biomechanical loads in field hockey SSGs in comparison to physiological loads.